Critical appraisal of United Kingdom clinical practice guidelines in kidney transplantation using the Appraisal of Guidelines for Research and Education (AGREE) II tool: A systematic review - Knight, S; Pengel, L; O'Callaghan, J; Morris, P (Wiley, 2017)
Purpose Patient specific instrumentation (PSI) has been proposed as a means of improving surgical accuracy and ease of implantation during technically challenging procedures such as unicompartmental knee arthroplasty (UKA). The purpose of this prospective randomised controlled trial (RCT) was to compare the accuracy of implantation and functional outcome of mobile bearing medial UKA s implanted with and without PSI by experienced UKA surgeons. Methods Mobile-bearing medial UKA s implanted were implanted in 43 patients using either PSI guides or conventional instrumentation. Intra-operative measurements, meniscal bearing size implanted, and post-operative radiographic analyses were performed to assess component positioning. Functional outcome was determined using the Oxford Knee Score (OKS). Results PSI guides could not be used in 3 cases due to concerns regarding accuracy and registration onto native anatomy, particularly on the tibial side. In general, similar component alignment and positioning was achieved using the two systems (n.s. for coronal/sagittal alignment and tibial coverage). The PSI group had greater tibial slope (p=0.029). The control group had a higher number of optimum size meniscal bearing inserted (95% versus 52%; p=0.001). There were no differences in OKS improvements (n.s). Conclusions Component positioning for the two groups was similar for the femur but less accurate on the tibial side using PSI, often with some unnecessarily deep resections of the tibial plateau. Although PSI was comparable to conventional instrumentation based on OKS improvements at 12-months, we continue to use conventional instrumentation for UKA at our institution until further improvements to the PSI guides can be demonstrated.